Antioxidant Properties of Agri-Food Byproducts and Specific Boosting Effects of Hydrolytic Treatments - Federica Moccia; Sarai Agustin-Salazar; Luisella Verotta; Enrico Caneva; Samuele Giovando; Gerardino D'Errico; Lucia Panzella; Marco d'Ischia; Alessandra Napolitano (MDPI AG, 2020)
Largely produced agri-food byproducts represent a sustainable and easily available source of phenolic compounds, such as lignins and tannins, endowed with potent antioxidant properties. We report herein the characterization of the antioxidant properties of nine plant-derived byproducts. 2,2-Diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing/antioxidant power (FRAP) assays indicated the superior activity of pomegranate peels and seeds, grape pomace and pecan nut shell. An increase in the antioxidant potency was observed for most of the waste materials following a hydrolytic treatment, with the exception of the condensed tannin-rich pecan nut shell and grape pomace. UV-Vis and HPLC investigation of the soluble fractions coupled with the results from IR analysis and chemical degradation approaches on the whole materials allowed to conclude that the improvement of the antioxidant properties was due not only to removal of non-active components (mainly carbohydrates), but also to structural modifications of the phenolic compounds. Parallel experiments run on natural and bioinspired model phenolic polymers suggested that these structural modifications positively impacted on the antioxidant properties of lignins and hydrolyzable tannins, whereas significant degradation of condensed tannin moieties occurred, likely responsible for the lowering of the reducing power observed for grape pomace and pecan nut shell. These results open new perspectives toward the exploitation and manipulation of agri-food byproducts for application as antioxidant additives in functional materials.